Relationships between demographic factors and emerging adult’s academic achievement - Hanafi, Zahyah (Human Resource Management Academic Research Society, 2016)
This study examines the impact of demographic factors on the academic achievement of students during their emerging adulthood.The sample includes 264 students between the ages of 18 to 25 years from Islamia University Bahawalpur and Bahauddin Zakariya University, Multan, Pakistan.Demographics factors are measured using Student Demographic Survey (SDS), and academic achievement (AA) is measured by Grade Point Average (GPA). Partial least square based on structural equation modelling technique (PLS-SEM) was used to analyse the data.The results confirmed the significant positive relationship between age, gender, mother’s education, location, parent’s income and academic achievement. This study concludes that female academic achievement is better compared to male and educated parents also contributed to enhancing the emerging adult’s academic achievement.Students with financially rich backgrounds are better performers in their academic pursuits than those from poor background. In addition, large family size also had adverse effects on academic performance